A novel image watermarking method based on center symmetric local binary pattern with minimum distortion - Tuncer, Turker; Kaya, Mustafa (Elsevier Gmbh, 2019)
In this study, a novel semi-fragile image-watermarking method based on Center-Symmetric Local Binary Patterns (CSLBP) in integer wavelet domain is proposed. Integer Wavelet Transform (IWT), block division, Center Symmetric Local Binary Pattern (CSLBP) based watermark embedding and extraction, watermarking key construction, watermarking key encryption using logistic map based Advanced Encryption Standard (AES), and watermarking key decryption techniques have been used in phases of the proposed method. Firstly, High-High (HH) sub-band is obtained by using Integer Wavelet Transform (IWT) with lifting scheme. HH sub-band is used to embed watermark for providing high visual quality. HH sub-band is divided into 4 x 4 size of non overlapping blocks. Then CSLBP based watermarking embedding is implemented to the blocks. Watermarking key is composed of CSLBP, and defined rules. These rules are defined to achieve high visual quality in the wavelet domain. In this work, logistic map based PIING is used to generate encryption key, and AES to provide confidentiality. In order, visual quality, robustness and confidentiality are considered for obtaining experimental results. The results clearly illustrated that the presented method is secure, semi-fragile watermarking method with high visual quality.
Keywords: CSLBP based image-watermarking; Semi fragile watermarking; Integer wavelet transform; Digital forensics